Association between body mass index and presence of skin disorders in schoolchildren - Miranda Souza, Luma; Alves dos Santos, Bruna; Firminia de Souza Almeida Agostinho de Mello, Isnaia; de Lima Botelho Filho, Carlos Alberto; Lopes, Johnnatas Mikael; Kedima Diniz Cavalcanti Tenório, Andrea; Pereira Tenório, Pedro (O Mundo da Saúde, 2022)
Obesity is a chronic, multifactorial and complex metabolic disorder, in which organic damage can be evident in the short or long term, especially dermatological disorders. With the objective of verifying the association between the body mass index and the presence of dermatological conditions, students at a public school in the backcountry of Bahia were studied. This was a cross-sectional study in which 169 schoolchildren were evaluated. The outcome was skin conditions, and the independent variables were BMI, age, and sex. Data were analyzed with the chi-squared test and an α≤0.05. About 41 students (24.3%) were underweight, 92 (54.4%) were eutrophic, and 36 (21.3%) were obese. Among the dermatological conditions, stretch marks stood out with a prevalence of 58%, followed by cellulite with 26%, and acne with 24.3%. The age group (14-20 years) was significantly associated with BMI values (p=0.05). Similarly, acanthosis (p=0.05), striae, hidradenitis, and cellulite also showed a significant relationship with BMI (p=0.01). There was statistical significance (p=0.01) when the presence of up to six dermatoses was compared with the low weight, eutrophic, and obese groups. Certain skin conditions were significantly associated with BMI. It is necessary to carry out educational awareness and prevention actions aimed at these young people that lead to a reduction in obesity cases, considering that in this group the dermatological changes were more evident.